Ecosofía: por una concepción sagrada de mundos - Patto, Ana (2024)
This essay was presented at the virtual meeting Guattari + 30, transversalidades latinocósmicas, held in 2022. In it, I present some conceptions of nature in Western thought, emphasizing the process of rationalization and instrumentalization that develops from modernity. The aim of the paper is to reflect on the ecosophical problem from a historical and philosophical journey that highlights the main conceptions of nature that underlie the predatory way in which we relate to it. On the other hand, it also presents other lines of thought that, from a more sacred conception of the world, serve as alternatives to think of new, more 'sustainable' modes of existence.